Association Between Fat-soluble Vitamins and Lipid Profile in the Overweight Population - Piran, Sadegh; Sarmasti, Sahar; Shabani, Mohammad; Kakavandi, Naser; Hosseni, Bita; Khosravi, Mohsen; Resaee, Shima; Soltanmohammadi, Elham; Naseri, Faezeh; Mohammadi, Asghar; Najafi, Mohammad (Recent Patents on Food, Nutrition & Agriculture, 2020)
Background & Aims: It is well-known that the coronary artery stenosis is related to lipid profile. This is a descriptive cross-sectional study to investigate the relationship between the serum fat-soluble vitamins (A, E and D), circulating proprotein convertase subtilisin/kexin type 9 (PCSK9), and lipid profile in the study population. Methods: A total of 120 overweight subjects were participated in this study. The circulating PCSK9 and vitamin D were measured by ELISA technique. The serum vitamin A and vitamin E amounts were simultaneously measured by the HPLC method. The Serum Small Dense LDLCholesterol (sdLDL-C) values were evaluated using heparin-Mg2+ precipitation technique. The lipid profile was measured by routine laboratory techniques. Results: The serum vitamin E values correlated significantly to vitamin A (r= 0.47, P= 0.0001), VLDL-C (r= 0.30, P= 0.002), total cholesterol (r= 0.309, P= 0.001), PCSK9 (r= 0.233, P= 0.01) and total triglyceride (r= 0.61, P= 0.0001) values. The circulating PCSK9 values correlated significantly to LDL-C (r= 0.17, P= 0.05) and total cholesterol (r= 0.23, P= 0.009) values. However, there were not correlations between the levels of serum D and A vitamins, the serum LDL-C, sdLDL-C and total cholesterol values. Conclusion: The data showed the correlations between serum vitamin E and PCSK9-related LDLC values lower than the normal range. Furthermore, the results suggested a nutritional need on the patents considering supplementation or fortification of vitamin E for the overweight subjects with higher LDL-C levels.
Keywords: sdLDL-C